What motivates millennials? How intersectionality shapes the working lives of female entrepreneurs in Canada's fashion industry. Issue 4 (3rd April 2019) - Brydges, Taylor; Hracs, Brian J.
Abstract: The contemporary fashion industry is based on a set of 'gendered skills and attributes.' Women numerically dominate fashion schools and the labour force of fashion firms, and also start and run the majority of independent fashion brands. Angela McRobbie and others have highlighted the importance of considering the gendered dynamics of fashion-related work. Yet, as the industry continues to evolve in the wake of global integration, the digital transition and intensifying competition, there is an ongoing need for research. Using an intersectional approach, this paper provides a novel case study of young 'Millennial' female independent fashion designers who operate within the emerging and under-explored Canadian fashion industry. Drawing on 87 interviews and participant observation, the paper demonstrates how entrepreneurial motivations, pathways, practices and experiences are shaped by individual characteristics, such as gender, age, lifecycle and class. Particular attention is paid to the challenges and tensions associated with the D.I.Y. (do it yourself) model and how forms of work, including aesthetic labour, are performed and experienced in virtual spaces such as social media platforms. In so doing, the paper contributes to nascent research on Millennials and nuances our understanding of the gendered nature of creative labour. Crucially, the paper also moves beyond typical masculinist conceptualisations of entrepreneurship, which focus on high-growth and high-technology businesses, to highlight the legitimacy, prevalence and importance of alternative motivations, networks, identities and business practices within contemporary markets and creative industries.